Two level full factorial design for the extraction of antioxidants from Decapterus maruadsi by product using wet rendering technique - Muhammad Nurfikri Alif, Abdullah; Zatul Iffah, Mohd Arshad; Nurul Aini, Mohd Azman (Universiti Malaysia Pahang, 2024)
The fish industry is a growing sector in Malaysia. However, the fishing industry produces a significant amount of fish waste that is often discarded directly into the sea, rivers, sewers, and land, causing environmental pollution. Fish waste can be transformed into useful items due to the existence of antioxidants and other essential substances. In this research, a two-level full factorial design was employed to recover antioxidants from Decapterus maruadsiwaste using wet rendering technique. Design Expert 7.0 software randomly allocated the variables into 16 experiments, with ABTS Radical Scavenging Assay as a response. Optimization for antioxidant activity yielded a 0.08% difference between experimental and projected values. In conclusion, Decapterus maruadsiwaste can be revalorized as a good source of antioxidants.